PARTISIPASI MASYARAKAT DALAM PROSES PEMBENTUKAN PERATURAN DESA DI KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Kalang, Thomas Boli; Stefanus, Kotan Y; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
Paticipation is a person’s involvement or participation mentally, thoughts, emotions or feelings that encourage him to contribute to achieving a common goal. However, in Nagawutung Districh there are still several villages where the people do not realize the importance pf their participation, and choose not to participatein in all activities in the village, especially participation in the process of forming of village regulations. Normative juridical method research is supported by empirical juridical reseach, namely: normative legal researchers whose legal rules are closely related to objects in a society which are then supported by the addition of empirical legal data. The results of the research show that community participation in five villages in Nagawutung district is very high,where at (1) the planning stage, only two villages had a large community, the while the other three villages did not participate, (2) at the discussion stage, it was found that only two villages had sufficient community participation. While the other three villages have quite low participation. In the formation of village regulations, three are several factors that hider the community. The inhibiting factors in these five villages are then divided into: internal factors and external factors. Internal factors include: level per type of work, and external factors are leadership.Based on the research results, it can be concluded that: The level of community participation in the five (5) very different villages in Nagawutung district will then determine different impacts on the resulting village regulation (perdes) products. So there are villages in Nagawutung district whose village regulation are comprehensive and well planned, and there are still vilages which are not yet comprehensive and not well planned, because there are still villages which are aware of the importance of participation even though some other villages are still not aware of participation ini developing their villagea. Through the establishment of village regulations.